Clinical consequences of polycystic ovary syndrome in menopause - Banaszewska, Beata; Pawelczyk, Leszek; Serdyńska, Monika; Spaczyński, Robert (Menopause Review/Przegląd Menopauzalny, 2002)
Polycystic ovary syndrome (PCOS) is the most common endocrine abnormality of premenopausal women. It has been established that hyperinsulinaemia is a fundamental disturbance in many women with polycystic ovary syndrome and has significant metabolic effect that could have an impact after the menopause. Women with a history of PCOS have higher levels of several cardiovascular risk factors including hyperlipidemia, diabetes, hypertension. Additionally, endometrial cancer, due to unopposed estrogen action is more common in patients with polycystic ovary syndrome. Early prevention and treatment of PCOS patients may avoid many serious postmenopausal consequnces.